Designing key model success factors in taekwondo sports with an emphasis on careful preparation - Goodarzi, G. R.; Mahmoudi, S. M.; Kordnaeij, A.; Saberi, A.; BabaShahi, J. (Journal of Advanced Pharmacy Education & Research, 2020)
The purpose of this article is to provide a comprehensive model for Designing key success factors in Taekwondo sports with an emphasis on Careful Preparation Was. Methodology: The research method was qualitative method which was done in the first stage according to the qualitative method of data collection. The statistical population of the study was executive level experts in taekwondo and university informants. The sampling method in the qualitative section was initially purposeful and judgmental, and then the snowball sampling method was used to collect information. In this study, the theoretical saturation was achieved by interviewing 21 of the samples. Data collection tools were interviews and documents, and after coding and identifying themes, they were used to design and validate the model. Data analysis was performed using related theme analysis methods and structural models were prepared. Then, the data from twenty-one interviews were coded and analyzed by theorized analysis method. Results: The results of content analysis showed that grouping codes is thirty-one components. Careful preparation One of the key factors Success Has been and has There are four sections that include the style and manner of the exercises, Participate in various competitions, Exercise recommendations and related tests. Conclusion: According to the research results, the proposed model can be used as an analytical tool Taekwondo sports with an emphasis on Careful preparation and physical exercise for competitions, it should be the basis of action to solve the problems of this field of sports in a scientific and principled way. Thus, the key factors of success in taekwondo sports were extracted and confirmed with emphasis on Careful preparation, and the research model was drawn and its suitability was confirmed. To succeed in taekwondo competitions, sports managers are advised to pay attention to the key factors of success in taekwondo sports with an emphasis on Careful preparation pay attention.